The Measurement of Inequality of Opportunity : Theory And An Application To Latin America - Ferreira, Francisco H. G. (The World Bank, 2008)
What part of the inequality observed in a particular country is due to unequal opportunities, rather than to differences in individual efforts or luck? This paper estimates a lower bound for the opportunity share of inequality in labor earnings, household income per capita and household consumption per capita in six Latin American countries. Following John Roemer, the authors associate inequality of opportunity with outcome differences that can be accounted for by morally irrelevant pre-determined circumstances, such as race, gender, place of birth, and family background. Thus defined, unequal opportunities account for between 24 and 50 percent of inequality in consumption expenditure in the sample. Brazil and Central America are more opportunity-unequal than Colombia, Ecuador, or Peru. "Opportunity profiles," which identify the social groups with the most limited opportunity sets, are shown to be distinct from poverty profiles: ethnic origin and the geography of birth are markedly more important as determinants of opportunity deprivation than of outcome poverty, particularly in Brazil, Guatemala, and Peru